A survey of individuals in US-based pharmaceutical industry HEOR departments: attitudes on policy topics. (October 2013) - Neumann, Peter J; Saret, Cayla J
We surveyed US-based leaders in health economics and outcomes research (HEOR) departments in drug and device companies to examine their views on the state of the field. We created a questionnaire that was emailed to 123 US-based senior HEOR professionals at 54 companies. Of the 123 recipients, 74 (60%) completed the survey. Most respondents (92%) expected their company's HEOR use to increase, and 80% reported that their organization's senior management viewed HEOR work as critical. Approximately 62% agreed that Academy of Managed Care Pharmacy (AMCP) dossiers are useful to US health plans, and 55% stated that Food and Drug Administration Modernization Act (FDAMA) Section 114 is useful. Approximately 49% believed the US government should use cost-effectiveness analysis in coverage and reimbursement decisions, but only 31% expected this to occur within 3 years. The findings suggest strong support for the function at senior management levels and optimism about the field.